2021
DOI: 10.5194/tc-15-303-2021
|View full text |Cite
|
Sign up to set email alerts
|

Full crystallographic orientation (<i>c</i> and <i>a</i> axes) of warm, coarse-grained ice in a shear-dominated setting: a case study, Storglaciären, Sweden

Abstract: Abstract. Microstructures provide key insights into understanding the mechanical behavior of ice. Crystallographic preferred orientation (CPO) develops during plastic deformation as ice deforms dominantly by dislocation glide on the basal plane, modified and often intensified by dynamic recrystallization. CPO patterns in fine-grained ice have been relatively well characterized and understood in experiments and nature, whereas CPO patterns in “warm” (T>-10∘C), coarse-grained, natural ice remain enigmatic. Pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 121 publications
6
39
1
Order By: Relevance
“…The study area, where warm, wet ice has moved a short distance along a wet bed presents extremely challenging conditions for fabric development. Yet, the presence of a discernible fabric in this setting indicates that crystallographic alignment should become prominent in larger glaciers ice streams and/or colder settings, consistent with results from, for example, (Hudleston, 1977), (Jackson and Kamb, 1997) and (Monz and others, 2021). Given the potential rheological impact of anisotropic ice (e.g.…”
Section: Implications For Fabric Formation In Other Settingssupporting
confidence: 75%
See 2 more Smart Citations
“…The study area, where warm, wet ice has moved a short distance along a wet bed presents extremely challenging conditions for fabric development. Yet, the presence of a discernible fabric in this setting indicates that crystallographic alignment should become prominent in larger glaciers ice streams and/or colder settings, consistent with results from, for example, (Hudleston, 1977), (Jackson and Kamb, 1997) and (Monz and others, 2021). Given the potential rheological impact of anisotropic ice (e.g.…”
Section: Implications For Fabric Formation In Other Settingssupporting
confidence: 75%
“…Although we cut most sections from a single layer of ice, for segments with very large grains (multi-cm), we cut strips from two or three segments spaced farther apart than the grain size in order to incorporate a greater number of grains in a single analysis (cf. Monz and others, 2021). We froze the sample to a similarly sized copper plate.…”
Section: Microanalysismentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with laboratory studies, shear strains in the marginal ice of Storglaciären are much higher, yet the ice is subjected to much lower natural strain rates. It is therefore likely that in natural settings, dynamic recrystallization is more evident, with the crystal orientation representing a smaller component of the overall shear history (Monz et al, 2021). Furthermore, Monz et al (2021) concluded that previous studies investigating crystal fabric in coarse-grained ice may have incorrectly reported multimaxima fabrics as a result of limited samples sizes and sampling bias.…”
Section: Microstructure and Crystal Fabric Of Glacier Icementioning
confidence: 99%
“…6(a)). Multiple-maxima ice c-axis fabrics arise when the number of grains measured from a single sample plane is not sufficient for a fully representative CPO (Monz et al, 2021). Cone and cluster CPOs are commonly observed in ice samples deformed under uniaxial compression conditions, and are thought to arise from varying contributions of strain-induced grain boundary migration (GBM) and grain rotation due to dislocation glide (Kamb, 1972;Vaughan et al, 2017).…”
Section: Crystallographic Controls and Effects Of Kinkingmentioning
confidence: 99%